A Comparative Study of the Film Adaptation and the Novel Source in "Love, Rosie" - Sabila Firdausa Safitri (Jurnal Bahasa, Sastra, dan Studi Amerika, 2025)
This research aims to point out the differences and similarities of the intrinsic elements between Love, Rosie novel and film adaptation as well as to identify the signs and their meanings in Love, Rosie film adaptation. This research uses a descriptive qualitative approach. The data were collected through close reading, observation, and finding details in Love, Rosie novel and film adaptation. The data analysis were conducted by comparing the novel and the film adaptation by finding the differences and similarities of the intrinsic elements between the novel source and the film adaptation as well as analyzing cinematography and mise en scène in Love, Rosie film adaptation and decoding the signs that are shown in the film. The findings suggest that there are differences and similarities of the intrinsic elements between the film adaptation and its literary source, furthermore, the signs in the film adaptation uncover the same theme to its literary source. The faithfulness of Love, Rosie film adaptation is established through the theme within the film through the narrative and the technical elements such as the cinematography and the mise en scène of the film.Keywords: novel, film, comparative, signs, faithfulness